Intimate partner violence among HIV positive women in care - results from a national survey, Uganda 2016 - Steven Ndugwa Kabwama; Justine Bukenya; Joseph K. B. Matovu; Violet Gwokyalya; Fredrick Makumbi; Jolly Beyeza-Kashesya; Shaban Mugerwa; John Baptist Bwanika; Rhoda K. Wanyenze (BMC, 2019)
Abstract Background Women remain disproportionally affected by the HIV/ AIDS epidemic because of sociocultural factors including violence perpetrated by intimate partners. Among HIVpositive (HIV+) women, intimate partner violence (IPV) affects engagement in care and reproductive health outcomes. We analyzed data from a national survey to estimate the prevalence of IPV among HIV+ women in care and associated factors. Methods The study was conducted among 5198 HIV+ women in care. Data were collected on socio-demographic characteristics, self-reported couple HIV status, mutual HIV status disclosure and IPV. IPV was assessed by asking participants whether their current husband or partner ever hit, slapped, kicked or did anything to hurt them physically, and whether their current husband or partner ever physically forced them to have intercourse or perform any sexual acts against their will. Women who responded "yes" were classified as having ever experienced IPV. Modified Poisson regression was used to identify factors associated with experiencing IPV. Results Of 5198 HIV+ women, 1664 (32.1%) had ever experienced physical violence, 1466 (28.3%) had ever experienced sexual violence and 2290 (44.2%) had ever experienced any IPV. Compared with women in relationships where the woman and their male partner were of the same age, women in relationships where the partner was ≥1 year younger were more likely to ever experience IPV (Prevalence risk ratio [PRR] = 1.43, 95% Confidence Interval [95%CI]: 1.10-1.71), as were women in relationships where the partner was < 10 years older (PRR = 1.20, 95%CI: 1.00-1.43) or ≥ 10 years older (PRR = 1.31, 95%CI: 1.05-1.64). Compared with women who did not have biological children, women with 3-4 biological children were more likely to have ever experienced IPV (PRR = 1.27 95%CI: 1.00-1.59) as were those with ≥5 biological children (PRR = 1.34, 95%CI: 1.06-1.71). Compared with women in sero-concordant relationships, women in sero-discordant relationships were less likely to ever experience IPV (PRR = 0.87 95%CI: 0.78-0.98). Conclusions In Uganda, a high proportion of HIV+ women have ever experienced IPV. Experiencing IPV was associated with circumstances related to the intimate relationship between the woman and her male partner. Health care workers should screen HIV+ women in care for IPV and offer appropriate psychosocial assistance.